Konsep Mata Kuliah Pengembangan Kepribadian Pendidikan Agama Islam - Pratiwi, Zulhaini Desi; Rusdi, Muhammad; Nisoh, Anan (Universitas Medan Area, 2024)
The concept of Islamic Education Personality Development Course focuses on shaping students' character, morality, and spirituality in alignment with Islamic teachings. It aims to instill core values such as integrity, discipline, empathy, and responsibility, serving as a foundation for students to become well-rounded individuals capable of contributing positively to society. Objectives and Scope The course seeks to: enhance students' understanding of Islamic teachings and their application in daily life, develop moral character and spiritual maturity in accordance with Islamic values, foster critical thinking and problem solving skills based on Islamic perspectives. The scope includes an exploration of foundational Islamic beliefs (aqidah), worship practices (ibadah), ethical guidelines (akhlaq), and their relevance in contemporary societal contexts. Teaching Methods and Evaluation, Interactive teaching methods, including lectures, group discussions, case studies, and reflective activities, are employed to encourage active participation and deeper understanding. Evaluation methods include written exams, individual and group assignments, practical assessments, and reflective journals to measure both theoretical understanding and practical application. Learning Materials Key topics include: Foundations of Islamic faith and worship practices, Ethical behavior and moral decision-making in Islam, The role of Islamic teachings in personal and social development, Contemporary challenges and the application of Islamic values. Relevance to Personality Development, The course is directly relevant to students’ personality development as it integrates spiritual and ethical dimensions into their educational journey. It equips students with the tools to navigate moral dilemmas, build meaningful relationships, and contribute to the community in ways that reflect Islamic principles. This holistic approach supports the cultivation of integrity, resilience, and leadership, preparing students to thrive in both personal and professional contexts. In conclusion, the course serves as a pivotal framework for fostering a balanced and principled personality among students, aligning academic pursuits with the values of Islamic teachings. Kata Kunci: Konsep, Kepribadian, agama